Przekształcanie wyrażeń algebraicznych :)- wzory skruconego mnozenia

a) -2(2a+3b-b)(3a+3b)-(a+b)²=

b) (x-y)²-(2x+3y-7)(4x-3x-2)+(2x+2y)(2x+3)=

c) 7(z+2w)(2z-3w-2)+(2z+4w)²=

d) 3(x+4y-5)(x-y)-(3x+2y)²=

e) 5(2k+2m-4)(k+2m)-(k-m)²

pomocy plis :):):):):)

dam naj...

1

Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T20:54:40+01:00
A) -2(2a+3b-b)(3a+3b)-(a+b)²=
-4a-6b+2b+3a+3b-2a-2b
-3a-3b

b) (x-y)²-(2x+3y-7)(4x-3x-2)+(2x+2y)(2x+3)=
2x-2y-2x-3y+7+4x-3x-2+2x+2y+2x+3=
5x-3y+8

c) 7(z+2w)(2z-3w-2)+(2z+4w)²=
7z+14w+2z-3w-2+4z+16w=
27w+13z-2

d) 3(x+4y-5)(x-y)-(3x+2y)²=
3x+12y-15+x-y-9x-4y=
-5x-7y-15

e) 5(2k+2m-4)(k+2m)-(k-m)²
10k+10m-20+k+2m-2k+2m
9k+14m-20
Mam nadzieję że wszystko będzie dobrze